Fibroepithelial tumours of the breast seen in a tertiary health centre in southwestern Nigeria - Olaofe, Olaejirinde O.; Soremekun, Ademola I.; Oladele, James O. (International Journal of Research in Medical Sciences, 2023)
Background: Fibroepithelial tumours of the breast are mainly fibroadenoma and phyllodes tumour. Our objective was to describe the clinical and pathological features of benign fibroepithelial tumours and then compare our findings with reports from other parts of the world. Methods: We carried out a retrospective study of all benign fibroepithelial tumours diagnosed in the Department of Morbid Anatomy and Forensic Medicine of Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Nigeria from January 1, 2018 to December 31, 2022. Results: A total of 538 cases of fibroadenoma were seen during the study period. Only 486 cases met the inclusion criteria and were then subsequently studied. Right sided tumour mass is seen in 203 (41.8%) patients, left sided masses in 173 (35.6%) patients and bilateral masses in 96 (19.8%) patients. The age of the patients ranges from 11 to 75 years. The average duration of symptoms is 16 months. The maximum length of fibroadenoma nodule ranges from 0.9cm to 15cm. The number of nodules seen in a patient range from 1 to 15. There is no association between the size of a fibroadenoma, number of the masses or the duration of symptoms before removal of the mass, and the age of the patient. Nineteen cases of phyllodes tumour were seen during the study period. Conclusions: Our study shows that fibroadenoma is the most common fibroepithelial tumour of the breast. A sizeable proportion of patients have bilateral tumours. Phyllodes tumour is much less common.